MECHANISMS OF CONTROL AND ASSESSMENT OF THE QUALITY OF EDUCATION IN EDUCATIONAL INSTITUTIONS (Scientific journal of the Fergana State University, 2023)
In this article, the concept of quality in the educational system, approaches to the problem of educational quality, mechanisms of quality control. In particular, a number of models for the evaluation of the activity of educational institutions, attestation and accreditation, as well as evaluation have been analyzed.